Diving Deep into Technology: A Systematic Literature Review on the Utilization of Chatbots in Education - Rais, Nabilah Nur Rahmah; Wedi, Agus; Praherdhiono, Henry (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
A chatbot is a piece of technology that mimics a conversation between a software application and a human. This technology has advanced quickly in recent years, and this technology has undergone significant advancements in recent years, particularly education. For this purpose, the researcher used the Systematic Literature Review (SLR) method to examine how this technology has developed and evolved over the past five years in the educational field. The findings of this study are intended to enable educators who want to create a conversational assistant for their course and developers who want to create chatbot systems for the educational space with a concise overview of the information acquired.